Development of rapid and simultaneous detection of four major foodborne pathogens using a multiplex PCR method - Aliakbar Rezaei; Samaneh Bina; Mohammad Javad Raee; Marzieh Rashedinia (Shiraz University of Medical Sciences, 2024)
Food borne diseases are an important public health problem has major impacts on human health, also affect trade and economic issues. Developing microbial cultures to detect foodborne pathogens is time-consuming and expensive. The aim of this study is to develop a multiplex (mPCR) method for the simultaneous detection of Staphylococcus aureus, Escherichia coli, Listeria monocytogenes and Salmonella enteritidis. Buffered peptone water (BPW) was used as pre-enrichment. Simplex and multiplex PCR settings were optimized and applied to both pure co-cultures and artificially inoculated ready-to-eat food samples (falafel and chicken nugget). The four microorganisms could be detected individually and in enrichment media artificially inoculated at 101 CFU/mL by mPCR. In conclusion, the individual and combined growth of E. coli, S. enterica, S. aureus and, L. monocytogenes with low levels of contamination in the presence of food matrices such as falafel and chicken nuggets is effectively supported by BPW broth as co-culture medium before mPCR detection. The proposed protocol for pre-enrichment of E. coli, S. enterica, S. aureus and, L. monocytogenes in takes approximately 34 hours , compared to culture methods that require at least 7 days. This notably reduces analysis time, effort, and cost.